2017
DOI: 10.1371/journal.pone.0186203
|View full text |Cite
|
Sign up to set email alerts
|

Process oriented guided inquiry learning (POGIL®) marginally effects student achievement measures but substantially increases the odds of passing a course

Abstract: While the inquiry approach to science teaching has been widely recommended as an epistemic mechanism to promote deep content understanding, there is also increased expectation that process and other transferable skills should be integral part of science pedagogy. To test the hypothesis that coupling process skills to content teaching impacts academic success measures, we meta-analyzed twenty-one studies (n = 21) involving 7876 students that compared Process Oriented Guided Inquiry Learning (POGIL), a pedagogy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 37 publications
6
64
1
1
Order By: Relevance
“…Among PLTL, POGIL and Flipped classes in chemistry, the weighted mean effect size indicates that a positive small to medium effect has been realized. It is also worth noting that the weighted mean effect size for POGIL of 0.30 is comparable to the 0.22 results observed in a recent meta‐analysis on POGIL implementation across disciplines (Walker & Warfa, ). The studies with nonspecified cooperative learning features 33 studies and a larger weighted mean effect size of 0.71.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Among PLTL, POGIL and Flipped classes in chemistry, the weighted mean effect size indicates that a positive small to medium effect has been realized. It is also worth noting that the weighted mean effect size for POGIL of 0.30 is comparable to the 0.22 results observed in a recent meta‐analysis on POGIL implementation across disciplines (Walker & Warfa, ). The studies with nonspecified cooperative learning features 33 studies and a larger weighted mean effect size of 0.71.…”
Section: Resultssupporting
confidence: 80%
“…Each chemistry specific meta‐analysis investigates a single EBIP (e.g., Peer‐Led Team Learning) and as a result each analyses 25 or fewer studies; this number of studies is comparable to the number of chemistry specific studies analyzed in meta‐analyses on the broader fields of science or STEM education. Other meta‐analyses have been conducted on POGIL (Walker & Warfa, ) and blended learning, combining face‐to‐face instruction with computer mediated instruction (Vo, Zhu, & Diep, ), but these analyses were not subject specific. Thus, the current literature is unable to provide a thorough synthesis of research on effective instructional practices particular to chemistry or evaluate the effectiveness of a particular EBIP in chemistry relative to other widely used EBIPs.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Studies have also found that POGIL transformed the classroom into an active learning zone with improved student performance in examinations and higher learning skills. 27,28 The academic caliber of the students in our study could have been a potential confounding factor in the results, but there was no statistically signiicant diference in the undergraduate marks of the two groups of students. Also, the end-of-year biostatistics and research methodology question paper may not be a confounding factor because the university has a well-organized question bank with structured key points that have been given to students at the beginning of their course; also, the questions were meticulously chosen according to the same diiculty level for both the groups of students.…”
Section: Discussionmentioning
confidence: 64%
“…Guided inquiry model with starter experiment approach in teaching science process skills of the students is effective, because it gives students a complex thinking space (Wardani & Djukri, 2019). So that by using a guided inquiry-based practicum guide, it can train students to find and solve several problems with the skills they have and guided inquiry stages that are in the guide when in their small group (Walker & Warfa, 2017). Accordance with the opinion Students work in small groups in the classroom or in the laboratory in an instructional module that presents information or data, followed by questions that lead are designed to guide students towards the formulation of conclusions (Khasanah, Susilaningsih, & Nuswowati, 2017).…”
Section: Resultsmentioning
confidence: 99%